Likok Pulo Aceh Dance as A Educational Media of Religious Values for Acehnese in Pulo Aceh - Basri, Novysa; Triyanto, Triyanto; Hartono, Hartono (Universitas Negeri Semarang, 2017)
The purpose of this research is to describe Likok Pulo Aceh dance as an educational media of religious values in Pulo Aceh society. This research used qualitative research method with interdisciplinary approach. The data was collected by observation, interview, and documentation. The researcher used triangulation to check the validity of data. Then it analyzed using reduction flow, data presentation, and data verification. The results showed that the messages that delivered from Likok Pulo Aceh dance through the dancers was when dancers perform the movement of the dance and poetry (syair), it gave advice to the Acehnese people especially in the people Pulo Aceh about Allah SWT’s rules and the relationship between the society. From the movements of dancers such as the movement of Saleum until the closing movement of Likok Pulo Aceh dance have some values which are aqidah, muamalah and morals and almost all the poems (lyric) which was sang by the dancers give some messages. The messages that conveyed relating to aqidah, mumalah and morals, especially the relationship between God and human being. Regarding to the relationship between Allah SWT and human being was how to pray in a good way and did not forsake for Salat and Shalawat to our Prophet Muhammad SAW. For young people or the future generations, they should not deny their parents, did not occupy the bad lust, for men and women there was a procedure of how to choose life companion that appropriate with the doctrine of Islam or the Shari’a. As long as the relationship between human and human, we should respect and always keep the hospitality to each other. This research is expected to instill these values ​​for next generation and keep on preserved.